Pemberian MP-ASI Dini dengan Kejadian Stunting pada Balita di Desa “TJ” Wilayah PKM “M” Lebak – Banten - Dini Rostianti Putri; Roslina Roslina (Akademi Kebidanan La Tansa Mashiro, 2020)
Malnutrition at an early age increases infant and child mortality, causes suffering, is easy to get sick and has poor posture as adults (Millennium Challenge Account Indonesia, 2018). The incidence of short toddlers or commonly referred to as stunting is one of the nutritional problems experienced by toddlers in the world today. In 2017, 22.2% or around 150.8 million children under five in the world were stunted. The average prevalence of stunting under five in Indonesia in 2005-2017 was 36.4% (Kemenkes RI, 2018). The purpose of this study was to determine the relationship between early complementary feeding and the incidence of stunting in children under five in the